Morphological and functional cardiac changes in TAVI follow-up: evaluation through transthoracic echocardiography - Fonseca, Virgínia (2018)
Background: Aortic stenosis is a valvular disease with increasing prevalence. The most common etiology of aortic stenosis is degenerative calcification of the leaflets due to lipid accumulation, fibrosis, and inflammation, usually present in older individuals, and has bad prognosis when becomes symptomatic. The replacement of the aortic valve is the first surgical therapeutic option for severe aortic stenosis, however, 30 to 40% of patients cannot accomplish by contraindications. Transcatheter aortic valve implantation (TAVI) is a treatment option for patients who cannot undergo surgical valve replacement. Objective: To describe and compare morphological and functional cardiac changes, through transthoracic echocardiography, in the follow-up after TAVI.